Wasabi: del ámbito gastronómico a las alarmas contra incendios - Ortiz Rodriguez, Bruno A. (2011)
A group of Japanese researchers has developed a fire alarm that does not depend on people’s audition, but on their sense of smell. This alarm releases allylisothiocyanate in spray to wake people up and hence inform them of a hazardous situation like a fire.